THE MODEL OF ENVIRONMENTAL DEVELOPMENT TO ENHANCE RESEARCH QUALITATIVE CLASSROOM ACTION RESEARCH OF TEACHERS IN THE EDUCATIONAL EXTENSION SCHOOLS UNDER THE OFFICE OF THE BASIC EDUCATION COMMISSION IN THE LOWER NORTHERN PROVINCE AREA - Chantaramanee, Wanida; Khamsorn, Sukkaew; Phukhao, Thirayut (Life Sciences and Environment Journal, 2017)
This research and development aims to study the condition and problems 2) to develop the model 3) to try out the model and 4) to evaluate the model of the environmental development for enhancing qualitative classroom action research of teachers. The research targets were extension schools under the Office of the Basic Education Commission in the lower northern Province area. The samples were 552 people who are administrators and teachers from 276 schools. The research instrument was 6 copies and analyzed by using mean, standard deviation, t-test dependent and content analysis to find the efficiency and effectiveness of the model. The findings were as follows: 1) The environmental development to enhance research qualitative classroom action research of teachers was at a high level; however, the problems of the research were at a high level in three components as follows: research emphasis, distinctive culture and clear goals that serve a coordinating function. 2) The environmental development model to enhance research qualitative classroom action research of teachers found that there were five language characteristics as follows: introduction, system, application of the model, evaluation and condition or limit. The model of the environmental development to enhance research qualitative classroom action research of teachers was highly efficient. 3) The trial out found that the quality of classroom action research after using the environmental development model to enhance research qualitative classroom action research of teachers was higher than before using the model with significantly different at 0.01 level 4) The evaluations of the model use of the environmental development to enhance research qualitative classroom action research of teachers were as follows: the evaluate the model was the highest efficient and effectiveness resulting to the environmental development to enhance research qualitative classroom action research was met with the 3 setting indicators which were input, process, and outcome.